Liquid crystal alignment treating agent, liquid crystal alignment film and liquid crystal display element
By using a specific compound with more than three thiol groups in the molecule and a liquid crystal orientation treatment agent with a polyimide precursor or polyimide, the problem of insufficient sealing properties of liquid crystal display elements under high temperature and high humidity conditions is solved, and high adhesion and stability are achieved.
Patent Information
- Application Number
- CN201980086389.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-27
- Filing Date
- 2019-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2039-12-24
AI Technical Summary
Under high temperature and high humidity conditions, the liquid crystal display element is prone to mixing water between the sealant and the liquid crystal alignment film, resulting in uneven display, bubble generation and component peeling.
A liquid crystal alignment treatment agent consisting of a specific compound containing more than three thiol groups in the molecule and a polyimide precursor or polyimide obtained by reacting a specific diamine with a tetracarboxylic acid is used to improve the adhesion between the liquid crystal alignment film and the sealant, and enhance the adhesion by ultraviolet light reaction.
High adhesion between the substrates of the liquid crystal display element is achieved, and bubble generation and component peeling can be suppressed under long-term exposure to high temperature and high humidity environment, thereby improving the stability and reliability of the liquid crystal display element.
Smart Images

Figure CN113260909B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal aligning agent used for producing a liquid crystal display element, a liquid crystal aligning film obtained from the liquid crystal aligning agent, and a liquid crystal display element using the liquid crystal aligning film. Background Art
[0002] Films made of organic materials such as polymer materials have attracted attention for their ease of formation and insulation performance, and are widely used as interlayer insulation films, protective films, etc. in electronic devices. Among them, organic films made of polyimide are used as liquid crystal alignment films in liquid crystal display elements that are well-known as display devices.
[0003] A liquid crystal alignment film is used for the purpose of controlling the alignment state of liquid crystals. However, as liquid crystal display elements become more precise, it is required to suppress a decrease in contrast of liquid crystal display elements and display defects caused by long-term use.
[0004] On the other hand, in a liquid crystal alignment film using polyimide, as a method for improving the liquid crystal orientation and making it difficult to produce display defects in the peripheral part of the liquid crystal display screen, a liquid crystal alignment film using a liquid crystal alignment agent added with an alkoxysilane compound has been proposed (see Patent Documents 1 and 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 61-171762
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 11-119226 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In recent years, liquid crystal display elements have been used for mobile applications such as smart phones and portable phones. In these applications, in order to ensure a display surface as wide as possible, it is necessary to set the width of the sealant between the substrates for bonding the liquid crystal display element to be narrower than before. In addition, based on the above reasons, it is also required to set the drawing position of the sealant to a position that is connected to the end of the liquid crystal alignment film with weak adhesion of the sealant, or to the upper part of the liquid crystal alignment film.
[0011] Therefore, in recent years, the bonding between the substrates of the liquid crystal display element has become weaker than before. Moreover, in such a case, due to the use under high temperature and high humidity conditions, water is easily mixed between the sealant and the liquid crystal alignment film, which is likely to cause uneven display near the frame of the liquid crystal display element, bubbles in the element, and further cause the element to peel off.
[0012] In view of this problem, as a method for improving the adhesion between the liquid crystal alignment film and the sealant, there is a method of adding an alkoxysilane compound to the liquid crystal alignment treating agent. However, when an alkoxysilane compound is added to the liquid crystal alignment treating agent, although the adhesion between the sealant and the liquid crystal alignment film can be improved, during the storage period of the liquid crystal alignment treating agent, the condensation reaction of the alkoxy group in the alkoxy compound will proceed, and there is a problem that the storage stability of the liquid crystal alignment treating agent deteriorates, such as the viscosity of the liquid crystal alignment treating agent increases and a gel is generated.
[0013] The object of the present invention is to provide a liquid crystal aligning agent for obtaining a liquid crystal aligning film having high adhesion (also referred to as close adhesion) between substrates and suppressing the generation of bubbles in a liquid crystal display element and the peeling of the element even when exposed to a high temperature and high humidity environment for a long time. In addition, it is also intended to provide a liquid crystal aligning film obtained by the above-mentioned liquid crystal aligning agent and a liquid crystal display element having the liquid crystal aligning film.
[0014] Solutions for solving problems
[0015] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have completed the present invention having the following gist.
[0016] That is, it is a liquid-crystal aligning agent containing the following (A) component and (B) component.
[0017] (A) Component: A compound having three or more thiol groups in the molecule (also referred to as a specific compound).
[0018] (B) Component: at least one polymer (also referred to as a specific polymer) selected from the group consisting of a polyimide precursor obtained by reaction of a diamine component containing a diamine having a structure (also referred to as a specific structure) of the following formula [1] with a tetracarboxylic acid component, and a polyimide obtained by imidating the polyimide precursor.
[0019]
[0020] (X 1 , X 3 Each independently represents a single bond, -O-, -NH-, -N(CH 3 )-、-CH 2 O-, -CONH-, -NHCO-, -CON(CH 3 )-、-N(CH 3 )CO-, -COO- or -OCO-. X 2represents an alkylene group having 1 to 18 carbon atoms, or an organic group having 6 to 24 carbon atoms having at least one cyclic group selected from a benzene ring, a cyclohexane ring, and a heterocyclic ring, wherein any hydrogen atom on these cyclic groups is optionally substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorinated alkyl group having 1 to 3 carbon atoms, a fluorinated alkoxy group having 1 to 3 carbon atoms, or a fluorine atom. 4 It represents a structure selected from the following formula [1-a] to formula [1-g].
[0021]
[0022] (X a represents a hydrogen atom or a benzene ring. b represents a single bond, a benzene ring, a cyclohexane ring or a heterocyclic ring. c represents an alkyl group having 1 to 18 carbon atoms, a fluorinated alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, or a fluorinated alkoxy group having 1 to 18 carbon atoms.
[0023] Effects of the Invention
[0024] According to the present invention, a liquid crystal display element can be obtained that has high adhesion between substrates, and can suppress the generation of bubbles and element peeling in the liquid crystal display element even when exposed to a high temperature and high humidity environment for a long time. Therefore, the element of the present invention is used for liquid crystal display elements of smart phones, mobile phones, etc.
[0025] The mechanism of why a liquid crystal display element having the above-mentioned excellent characteristics is obtained according to the present invention is not necessarily clear, but can be roughly estimated as follows.
[0026] Since the specific compound has a thiol group, the adhesion between the liquid crystal alignment film obtained by the liquid crystal alignment agent containing the compound and the metal electrode becomes high. In addition, the thiol group can be bonded to X in the specific structure of the specific polymer by ultraviolet rays or heat. 4 Therefore, the specific compound that improves the adhesion with the metal electrode can be chemically bonded with the specific polymer that becomes the base of the liquid crystal alignment film. As a result, stronger adhesion can be obtained.
[0027] Furthermore, the thiol group in a specific compound and the X in a specific structure 4 Since the photoreaction is carried out by ultraviolet rays, the sealant reacts with the reactive group of the polymerizable compound in the sealant by curing treatment of the sealant in manufacturing the liquid crystal display element, specifically, by irradiation with ultraviolet rays, and the adhesion between the liquid crystal alignment film and the sealant becomes strong.
[0028] Therefore, it can be considered that after the liquid crystal alignment film is formed, the adhesion between the liquid crystal alignment film and the metal electrode and the liquid crystal alignment film and the sealant becomes higher, and the liquid crystal display element can suppress the generation of bubbles and element peeling even when exposed to a high temperature and high humidity environment for a long time. DETAILED DESCRIPTION
[0029] <Specified compounds>
[0030] The specific compound is a compound having three or more thiol groups in the molecule.
[0031] Specifically, 1,2,3-propanetrithiol, 1,2,4-butanetrithiol, pentaerythritol tris(3-mercaptopropionate), 1,3,5-benzenetrithiol, 2,4,6-mesitylenetrithiol, neopentanetetrathiol, 2,4,6-toluenetrithiol, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), diquaternary Pentaerythritol hexa(3-mercaptopropionate), trimethylolpropane tri(3-mercaptobutyrate), trimethylolethane tri(3-mercaptobutyrate), pentaerythritol tetra(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6-(1H.3H.5H)-trione, 2,2'-bis(mercaptomethyl)-1,3-propanedithiol, pentaerythritol tetra(3-mercaptopropionate) or dipentaerythritol hexa(3-mercaptopropionate).
[0032] Among them, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6-(1H.3H.5H)-trione or neopentyltetramercaptan, pentaerythritol tetrakis(3-mercaptopropionate) or dipentaerythritol hexa(3-mercaptopropionate).
[0033] From the aspect of the adhesion between the liquid crystal alignment film of the liquid crystal display element and the metal electrode, the use ratio of the specific compound is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the specific polymer. It is more preferably 0.5 to 20 parts by mass. It is most preferably 1 to 15 parts by mass. In addition, the specific compound can be used alone or in combination of two or more according to various characteristics.
[0034] <Specific structure>
[0035] The specific structure is represented by the formula [1]. In the formula [1], X 1 , X 2 , X 3 , X 4 As defined above. Among them, preferably, they are as follows.
[0036] X 1 Preferred are single bonds, -O-, -CH 2 O-, -CONH-, -CON(CH 3 )- or -COO-, and from the viewpoint of ease of synthesis, a single bond, -O-, -CH 2 O-or-COO-.
[0037] X 2 It is preferably an alkylene group having 2 to 12 carbon atoms or an organic group having 6 to 24 carbon atoms having at least one cyclic group selected from a benzene ring and a cyclohexane ring. From the perspective of ease of synthesis and adhesion between the liquid crystal alignment film of the liquid crystal display element and the sealant, an alkylene group having 2 to 12 carbon atoms is more preferred.
[0038] X 3 Preferred are single bonds, -O-, -NHCO-, -N(CH 3 From the viewpoint of ease of synthesis, a single bond, -O-, -NHCO- or -OCO- is more preferable.
[0039] X 4 Preferred are the above-mentioned formula [1-a], formula [1-b], formula [1-d] or formula [1-e]. From the viewpoint of ease of synthesis and adhesion between the liquid crystal alignment film of the liquid crystal display element and the sealant, more preferred are formula [1-a], formula [1-b] or formula [1-e].
[0040] The preferred X in formula [1] 1 ~X 4 The combinations are shown in Tables 1 to 3 below.
[0041] [Table 1]
[0042] <![CDATA[X 1 ]]> <![CDATA[X 2 ]]> <![CDATA[X 3 ]]> <![CDATA[X 4 ]]> 1-1a single bond Alkylene having 2 to 12 carbon atoms single bond Formula [1-a] 1-2a single bond Alkylene having 2 to 12 carbon atoms -O- Formula [1-a] 1-3a single bond Alkylene having 2 to 12 carbon atoms NHCO Formula [1-a] 1-4a single bond Alkylene having 2 to 12 carbon atoms OCO- Formula [1-a] 1-5a single bond Alkylene having 2 to 12 carbon atoms single bond Formula [1-b] 1-6a single bond Alkylene having 2 to 12 carbon atoms -O- Formula [1-b] 1-7a single bond Alkylene having 2 to 12 carbon atoms NHCO Formula [1-b] 1-8a single bond Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-b] 1-9a single bond Alkylene having 2 to 12 carbon atoms single bond Formula [1-e] 1-10a single bond Alkylene having 2 to 12 carbon atoms -O- Formula [1-e] 1-11a single bond Alkylene having 2 to 12 carbon atoms -NHCO Formula [1-e] 1-12a single bond Alkylene having 2 to 12 carbon atoms OCO- Formula [1-e] 1-13a -O- Alkylene having 2 to 12 carbon atoms single bond Formula [1-a] 1-14a -O- Alkylene having 2 to 12 carbon atoms -O- Formula [1-a] 1-15a -O- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-a] 1-16a -O- Alkylene having 2 to 12 carbon atoms OCO- Formula [1-a]
[0043] [Table 2]
[0044] <![CDATA[X 1 ]]> <![CDATA[X 2 ]]> <![CDATA[X 3 ]]> <![CDATA[X 4 ]]> 1-17a -O- Alkylene having 2 to 12 carbon atoms single bond Formula [1-b] 1-18a -O- Alkylene having 2 to 12 carbon atoms -O- Formula [1-b] 1-19a -O- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-b] 1-20a -O- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-b] 1-21a -O- Alkylene having 2 to 12 carbon atoms single bond Formula [1-e] 1-22a -O- Alkylene having 2 to 12 carbon atoms -O- Formula [1-e] 1-23a -O- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-e] 1-24a -o- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-e] 1-25a -CH2O- Alkylene having 2 to 12 carbon atoms single bond Formula [1-a] 1-26a -CH2O- Alkylene having 2 to 12 carbon atoms -O- Formula [1-a] 1-27a -CH2O- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-a] 1-28a -CH2O- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-a] 1-29a -CH2O- Alkylene having 2 to 12 carbon atoms single bond Formula [1-b] 1-30a -CH2O- Alkylene having 2 to 12 carbon atoms -O- Formula [1-b] 1-31a -CH2O- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-b] 1-32a -CH2O- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-b]
[0045] [Table 3]
[0046] <![CDATA[X 1 ]]> <![CDATA[X 2 ]]> <![CDATA[X 3 ]]> <![CDATA[X 4 <!-- 4 -->]]> 1-33a -CH2O- Alkylene having 2 to 12 carbon atoms single bond Formula [1-e] 1-34a -CH2O- Alkylene having 2 to 12 carbon atoms -O- Formula [1-e] 1-35a -CH2O- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-e] 1-36a -CH2O- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-e] 1-37a -COO- Alkylene having 2 to 12 carbon atoms single bond Formula [1-a] 1-38a -COO- Alkylene having 2 to 12 carbon atoms -O- Formula [1-a] 1-39a -COO- Alkylene with 2 to 12 carbon atoms -NHCO- Formula [1-a] 1-40a -COO- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-a] 1-41a -COO- Alkylene having 2 to 12 carbon atoms single bond Formula [1-b] 1-42a -COO- Alkylene having 2 to 12 carbon atoms -O- Formula [1-b] 1-43a -COO- Subunits with 2 to 12 carbon atoms -NHCO- Formula [1-b] 1-44a -COO- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-b] 1-45a -COO- Alkylene having 2 to 12 carbon atoms single bond Formula [1-e] 1-46a -COO- Alkylene having 2 to 12 carbon atoms -O- Formula [1-e] 1-47a -COO- Alkylene having 2 to 12 carbon atoms -NHCO- Formula [1-e] 1-48a -COO- Alkylene having 2 to 12 carbon atoms -OCO- Formula [1-e]
[0047] Just X 1 ~X4 As for the combinations, the preferred ones are (1-2a) to (1-4a), (1-6a) to (1-8a), (1-10a) to (1-12a), (1-14a) to (1-16a), (1-18a) to (1-20a), (1-22a) to (1-24a), (1-26a) to (1-28a), (1-30a) to (1-32a), (1-34a) to (1-36a), (1-38a) to (1-40a), (1-42a) to (1-44a) or (1-46a) to (1-48a).
[0048] More preferred are combinations of (1-3a), (1-4a), (1-7a), (1-8a), (1-11a), (1-12a), (1-15a), (1-16a), (1-19a) to (1-21a), (1-23a), (1-24a), (1-27a), (1-28a), (1-31a) to (1-33a), (1-35a), (1-36a), (1-39a), (1-40a), (1-43a) to (1-45a), (1-47a) or (1-48a).
[0049] From the perspective of ease of synthesis and the adhesion between the liquid crystal orientation film of the liquid crystal display element and the sealant, the most preferred combination is (1-20a), (1-21a), (1-28a), (1-32a), (1-33a), (1-40a), (1-44a) or (1-45a).
[0050] <Specific polymer>
[0051] The specific polymer is a polyimide precursor obtained by a reaction of a diamine component containing a specific diamine with a tetracarboxylic acid component, or a polyimide obtained by imidating the polyimide precursor.
[0052] The polyimide precursor has a structure of the following formula [A].
[0053]
[0054] In formula [A], R 1 Represents a tetravalent organic group. 2 Represents a divalent organic group. 1 and A 2 Each of them represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms. 3 and A 4 Each of them represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or an acetyl group. n represents a positive integer.
[0055] The diamine component is a diamine having two primary or secondary amino groups in the molecule, and the tetracarboxylic acid component includes a tetracarboxylic acid compound, tetracarboxylic dianhydride, a tetracarboxylic acid dihalide compound, a tetracarboxylic acid dialkyl ester compound, or a tetracarboxylic acid dialkyl ester dihalide compound.
[0056] The polyimide polymer is preferably a polyamic acid having a repeating unit structure of the following formula [D] or a polyimide obtained by imidizing the polyamic acid because it can be easily obtained by using tetracarboxylic dianhydride of the following formula [B] and diamine of the following formula [C] as raw materials.
[0057]
[0058] (R 1 and R 2 and R defined in formula [A] 1 and R 2 same.)
[0059]
[0060] (R 1 and R 2 and R defined in formula [A] 1 and R 2 same.)
[0061] In addition, A in formula [A] can also be introduced into the polymer of formula [D] obtained above by a conventional synthesis method. 1 and A 2 an alkyl group having 1 to 8 carbon atoms, and A in the formula [A] 3 and A 4 An alkyl group having 1 to 5 carbon atoms or an acetyl group.
[0062] As a method for introducing a specific structure into a polyimide-based polymer, it is preferable to use a diamine having a specific structure as part of the raw materials. In particular, it is preferable to use a diamine of the following formula [1a] (also referred to as a specific diamine).
[0063]
[0064] Y represents the formula [1], X 1 ~X 4 The definitions and preferred combinations are as described in formula [1].
[0065] n represents an integer of 1 to 4. Among them, the integer 1 is preferred.
[0066] As a preferable specific example of a specific diamine, the diamine of following formula [1a-1] - formula [1a-9] is mentioned.
[0067]
[0068] (n each independently represents an integer from 2 to 12.)
[0069] Among them, from the viewpoint of the adhesion between the liquid crystal alignment film of the liquid crystal display element and the sealant, the diamine of formula [1a-1], formula [1a-2], formula [1a-5], formula [1a-6] or formula [1a-9] is preferred. In this case, n in the formula is preferably an integer of 2 to 10, each independently.
[0070] From the viewpoint of the adhesion between the liquid crystal alignment film of the liquid crystal display element and the sealant, the usage ratio of the specific diamine is preferably 1 to 50 mol % relative to the entire diamine component, more preferably 1 to 40 mol %, particularly preferably 5 to 40 mol %. In addition, the specific diamine may be used alone or in combination of two or more depending on the characteristics.
[0071] As a diamine component for preparing a specific polymer, a diamine other than a specific diamine (also referred to as other diamines) may also be included. Specifically, diamine compounds of formula [3a-1] to [3a-5] described on pages 34 to 38 of International Publication WO2016 / 076412, other diamine compounds described on pages 39 to 42 of the publication, and diamine compounds of formula [DA1] to [DA15] described on pages 42 to 44 of the publication can be listed. These diamine components can be used alone or in combination of two or more according to their properties.
[0072] The tetracarboxylic acid component used for preparing the specific polymer is not particularly limited, and specific examples thereof include tetracarboxylic dianhydride of formula [4] described on pages 44 to 45 of International Publication WO2016 / 076412 and other tetracarboxylic acid components described on pages 45 to 46. These tetracarboxylic acid components can be used alone or in combination of two or more depending on the properties.
[0073] The method for synthesizing a specific polymer is not particularly limited. Usually, it is obtained by reacting a diamine component with a tetracarboxylic acid component. Specifically, the method described in pages 46 to 50 of International Publication WO2016 / 076412 can be cited.
[0074] The reaction of a diamine component and a tetracarboxylic acid component is usually performed in a solvent containing a diamine component and a tetracarboxylic acid component. As a solvent used at this time, there is no particular limitation as long as it is a solvent in which the generated polyimide precursor can be dissolved.
[0075] Specifically, examples thereof include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,3-dimethyl-imidazolidinone, etc. In addition, when the polyimide precursor has high solvent solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or solvents of the following formulas [D1] to [D3] can be used.
[0076]
[0077] (D 1 and D 2 It represents an alkyl group having 1 to 3 carbon atoms. 3 represents an alkyl group having 1 to 4 carbon atoms. )
[0078] In addition, they can be used alone or in combination. Moreover, even if it is a solvent that does not dissolve the polyimide precursor, it can be mixed with the solvent in a range where the generated polyimide precursor does not precipitate. In addition, the moisture in the organic solvent hinders the polymerization reaction and becomes the cause of hydrolysis of the generated polyimide precursor, so the organic solvent is preferably a dehydrated organic solvent.
[0079] In the polymerization reaction of the polyimide precursor, when the total number of moles of the diamine components is 1.0, it is preferred that the total number of moles of the tetracarboxylic acid components is 0.8-1.2.
[0080] Polyimide is a polyimide obtained by ring-closing a polyimide precursor. In the case of polyimide, the ring-closing rate of the amic acid group (also referred to as the imidization rate) does not necessarily have to be 100%, and can be arbitrarily adjusted according to the use and purpose. Among them, from the perspective of the solubility of the polyimide polymer in the solvent, the ring-closing rate of the amic acid group is preferably 30 to 80%. More preferably, it is 40 to 70%.
[0081] The molecular weight of the specific polymer is preferably 5,000 to 1,000,000, more preferably 10,000 to 150,000, as measured by a weight average molecular weight by GPC (Gel Permeation Chromatography) method, in consideration of the strength of the resulting liquid crystal alignment film, workability during formation of the liquid crystal alignment film, and coating properties.
[0082] <Liquid crystal alignment agent>
[0083] The liquid crystal aligning agent is a solution for forming a liquid crystal aligning film, and is a solution containing a specific compound, a specific polymer, and a solvent. In this case, two or more specific compounds and specific polymers may be used respectively.
[0084] The content of the solvent in the liquid crystal aligning agent can be appropriately selected from the perspective of the coating method of the liquid crystal aligning agent and the viewpoint of obtaining the target film thickness. Among them, from the viewpoint of forming a uniform liquid crystal aligning film by coating, the content of the solvent in the liquid crystal aligning agent is preferably 50 to 99.9% by mass. Among them, preferably 60 to 99% by mass. More preferably 65 to 99% by mass.
[0085] The solvent used for the liquid-crystal aligning agent will not be particularly limited as long as it is a solvent which dissolves a specific compound and a specific polymer. Among them, it is preferable to use the following solvent (also referred to as solvent A).
[0086] For example, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, etc. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone is preferred. In addition, they can be used alone or in combination.
[0087] When the solubility of the specific polymer in the solvent is high, the following solvents (also referred to as solvent B) can be used.
[0088] Specific examples of solvent B include solvents B described in International Publication No. WO2014 / 171493, pages 58 to 60. Among them, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, dipropylene glycol dimethyl ether, cyclohexanone, cyclopentanone, or the above-mentioned formulas [D1] to [D3] are preferred.
[0089] Moreover, when using these solvents B, it is preferable to use N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone or γ-butyrolactone of the above-mentioned solvent A together for the purpose of improving the coating property of a liquid-crystal aligning agent.
[0090] These solvents B can improve the coating properties and surface smoothness of the liquid crystal alignment film when the liquid crystal alignment agent is applied, so when a polyimide precursor, polyimide, polyamide or polyester is used in the polymer, it is preferably used in combination with the solvent A. In this case, the solvent B is preferably 1 to 99% by mass of the total solvent contained in the liquid crystal alignment agent. Among them, it is preferably 10 to 99% by mass, and more preferably 20 to 95% by mass.
[0091] In the liquid crystal alignment agent, in order to improve the film strength of the liquid crystal alignment film, it is preferred to introduce a compound having an epoxy group, an isocyanate group, an oxetane group, a cyclocarbonate group, a hydroxyl group, a hydroxyalkyl group or a lower alkoxyalkyl group (collectively referred to as a crosslinking compound). At this time, the above-mentioned groups need to have two or more in the compound.
[0092] That is, the liquid crystal aligning agent preferably contains at least one crosslinking compound composed of a compound having two or more groups selected from an epoxy group, an isocyanate group, an oxetane group, a cyclocarbonate group, a hydroxyl group, a hydroxyalkyl group, an alkoxyalkyl group having 1 to 3 carbon atoms, or a polymerizable unsaturated bond group.
[0093] Specific examples of the crosslinkable compound having an epoxy group or an isocyanate group include crosslinkable compounds having an epoxy group or an isocyanate group described on pages 63 to 64 of International Publication WO2014 / 171493.
[0094] Specific examples of the crosslinkable compound having an oxetane group include crosslinkable compounds of formula [4a] to [4k] described on pages 58 to 59 of International Publication WO2011 / 132751.
[0095] Specific examples of the crosslinkable compound having a cyclic carbonate group include crosslinkable compounds of formula [5-1] to [5-42] described on pages 76 to 82 of International Publication WO2012 / 014898.
[0096] Specific examples of the crosslinkable compound having a hydroxyl group, a hydroxyalkyl group, and a lower alkoxyalkyl group include melamine derivatives or benzoguanamine derivatives described on pages 65 to 66 of International Publication No. 2014 / 171493 and crosslinkable compounds of formulas [6-1] to [6-48] described on pages 62 to 66 of International Publication No. WO2011 / 132751.
[0097] The content of the crosslinking compound in the liquid crystal aligning agent is preferably 0.1 to 100 parts by mass relative to 100 parts by mass of all polymer components. In order to allow the crosslinking reaction to proceed and achieve the desired effect, the content of the crosslinking compound in the liquid crystal aligning agent is more preferably 0.1 to 50 parts by mass, and most preferably 1 to 30 parts by mass relative to 100 parts by mass of all polymer components.
[0098] The liquid crystal aligning agent may contain a compound that improves the uniformity of the film thickness and the surface smoothness of the liquid crystal aligning film when the liquid crystal aligning agent is applied, or a compound that improves the adhesion between the liquid crystal aligning film and the electrode substrate.
[0099] As compounds for improving the uniformity of the film thickness and the surface smoothness of the liquid crystal alignment film, fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc. can be cited. Specifically, surfactants described on page 67 of International Publication WO2014 / 171493 can be cited. In addition, the use ratio is preferably 0.01 to 2 parts by mass relative to 100 parts by mass of all polymer components contained in the liquid crystal alignment agent. More preferably, it is 0.01 to 1 part by mass.
[0100] Specific examples of compounds that improve the adhesion between the liquid crystal alignment film and the electrode substrate include compounds described on pages 67 to 69 of International Publication WO2014 / 171493. In addition, the use ratio thereof is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of all polymer components contained in the liquid crystal alignment agent. More preferably, it is 1 to 20 parts by mass.
[0101] In the liquid-crystal aligning agent, in addition to the compounds other than those described above, a dielectric or a conductive substance for the purpose of changing the electrical properties such as the dielectric constant and conductivity of the liquid crystal aligning film may be added.
[0102] <Liquid crystal alignment film / liquid crystal display element>
[0103] The liquid crystal aligning agent can be used as a liquid crystal aligning film by applying it on a substrate, baking it, and then performing an alignment treatment by rubbing, light irradiation, etc. Moreover, in the case of vertical alignment applications, it can be used as a liquid crystal aligning film even without performing an alignment treatment.
[0104] As the substrate used at this time, there is no particular limitation as long as it is a substrate with high transparency. In addition to glass substrates, plastic substrates such as acrylic substrates, polycarbonate substrates, and PET (polyethylene terephthalate) substrates can also be used, and further, their films can also be used. In addition, from the viewpoint of process simplification, it is preferred to use metal electrodes and organic conductive films such as ITO electrodes, IZO (Indium Zinc Oxide: Indium Zinc Oxide) electrodes and IGZO (Indium Gallium Zinc Oxide: Indium Gallium Zinc Oxide) electrodes formed for liquid crystal driving. In addition, in the case of a reflective liquid crystal display element, if only a single-sided substrate is used, a substrate formed with a metal or dielectric multilayer film such as a silicon wafer or aluminum can be used.
[0105] The coating method of the liquid crystal alignment agent is not particularly limited, but is generally performed industrially by screen printing, offset printing, flexographic printing or inkjet method, etc. As other coating methods, there are dipping method, roll coating method, slit coating method, spin coating method or spray method, etc., which can be used according to the purpose.
[0106] After the liquid crystal alignment agent is coated on the substrate, the solvent can be evaporated at a temperature of 30 to 300° C., preferably 30 to 250° C., to form a liquid crystal alignment film, depending on the solvent used for the liquid crystal alignment agent.
[0107] If the thickness of the liquid crystal alignment film after firing is too thick, it becomes disadvantageous in terms of power consumption of the liquid crystal display element, and if the thickness is too thin, the reliability of the liquid crystal display element may decrease. Therefore, it is preferably 5 to 300 nm, and more preferably 10 to 200 nm.
[0108] When the liquid crystal is horizontally aligned or tiltedly aligned, the liquid crystal alignment film after baking is processed by rubbing or irradiation with polarized ultraviolet rays.
[0109] The liquid crystal used for the liquid crystal display element is not particularly limited, for example, nematic liquid crystal, smectic liquid crystal or cholesteric liquid crystal can be used. At this time, liquid crystal with positive or negative dielectric anisotropy can be selected according to the method of the liquid crystal display element. In addition, a guest-host liquid crystal display element in which a dichroic dye is dissolved in the liquid crystal can also be used.
[0110] The method for injecting liquid crystal is not particularly limited, for example, the following methods can be cited. That is, a pair of substrates formed with a liquid crystal alignment film are prepared, and a portion of the four sides of the substrate on one side are removed to apply a sealant, and then the substrate on the other side is bonded in such a way that the liquid crystal alignment film surface becomes the inner side, and an empty cell (cell) is made. Then, a method of injecting liquid crystal under reduced pressure from a position where a sealant is not applied to obtain a liquid crystal injection unit can be cited. In addition, the following method can also be cited: a pair of substrates formed with a liquid crystal alignment film are prepared, and liquid crystal is dripped on the top of the substrate on one side by ODF (One Drop Filling: liquid crystal dripping) method, inkjet method, etc., and then, the substrate on the other side is bonded to obtain a liquid crystal injection unit.
[0111] The method of controlling the gap of the liquid crystal display element is not particularly limited, and examples thereof include: a method of introducing a spacer of a target size into the liquid crystal, a method of applying to a substrate having a column spacer of a target size, a method of using a liquid crystal containing a column spacer of a target size, etc.
[0112] The size of the gap of the liquid crystal display element is preferably 1 to 100 μm. It is more preferably 1 to 50 μm. It is particularly preferably 2 to 30 μm. If the gap is too small, the contrast of the liquid crystal display element decreases, and if the gap is too large, the driving voltage of the element increases.
[0113] [Example]
[0114] The present invention will be described in further detail below with reference to Examples, but the present invention is not limited thereto. The abbreviations used below are as follows.
[0115] "Specific compounds"
[0116] A1: Karenz MTPE1 (manufactured by Showa Denko K.K.) / pentaerythritol tetrakis(3-mercaptobutyrate).
[0117] A2: DPMP (manufactured by SC Organic Chemical Co., Ltd.) / dipentaerythritol hexa(3-mercaptopropionate).
[0118] "Thiol group-containing compound"
[0119] a1: Karenz MTBD1 (manufactured by Showa Denko K.K.) / 1,4-bis(3-mercaptobutyryloxy)butane.
[0120] <Specific diamine>
[0121]
[0122] <Other diamines>
[0123]
[0124] <Tetracarboxylic acid component>
[0125]
[0126] "Cross-linking compounds"
[0127]
[0128] "Solvent"
[0129] NMP: N-methyl-2-pyrrolidone, NEP: N-ethyl-2-pyrrolidone.
[0130] BCS: ethylene glycol monobutyl ether.
[0131] PB: Propylene glycol monobutyl ether.
[0132] "Determination of Molecular Weight of Polyimide-Based Polymers"
[0133] The measurement was performed as follows using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803, KD-805) (manufactured by Shodex Corporation).
[0134] Column temperature: 50°C.
[0135] Eluent: N, N'-dimethylformamide (as an additive, lithium bromide monohydrate (LiBr·H 2 O) is 30mmol / L (liter), phosphoric acid / anhydrous crystals (o-phosphoric acid) is 30mmol / L, and tetrahydrofuran (THF) is 10ml / L).
[0136] Flow rate: 1.0 ml / min.
[0137] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000 and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight; about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratories).
[0138] "Determination of Imidization Rate"
[0139] Add 20 mg of polyimide powder to an NMR (nuclear magnetic resonance) sample tube (NMR standard sampling tube, φ5 (manufactured by Kusano Scientific Co., Ltd.)), add deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) (0.53 ml), and apply ultrasound to completely dissolve it. The solution was measured for 500 MHz proton NMR using an NMR measuring machine (JNW-ECA500) (manufactured by JEOL DATUM Co., Ltd.). The imidization rate was calculated as follows: the proton derived from the structure that does not change before and after imidization is determined as the reference proton, and the peak integral value of the proton and the proton peak integral value derived from the NH group of the amide acid appearing near 9.5 ppm to 10.0 ppm are used to calculate it using the following formula.
[0140] Imidization rate (%) = (1-α·x / y) × 100
[0141] (x is the peak integral value of protons derived from the NH group of the amic acid, y is the peak integral value of the reference proton, and α is the ratio of the number of reference protons to one NH proton of the amic acid in the case of polyamic acid (imidization ratio 0%).)
[0142] "Synthesis of polyimide polymers"
[0143] <Synthesis example 1>
[0144] D1 (2.20 g, 11.2 mmol), B1 (0.61 g, 2.31 mmol), C1 (0.25 g, 2.31 mmol) and C2 (1.99 g, 6.95 mmol) were mixed in NMP (15.1 g) and reacted at 25° C. for 8 hours to obtain a polyamic acid solution (1) having a resin solid content concentration of 25% by mass. The number average molecular weight (also referred to as Mn) of the polyamic acid was 26,300, and the weight average molecular weight (also referred to as Mw) was 80,800.
[0145] <Synthesis example 2>
[0146] D2 (1.05 g, 4.20 mmol), B1 (0.57 g, 2.16 mmol), C1 (0.23 g, 2.13 mmol) and C2 (4.96 g, 17.3 mmol) were mixed in NMP (20.3 g), reacted at 60° C. for 4 hours, then D1 (3.30 g, 16.8 mmol) and NMP (10.1 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (2) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 25,900 and an Mw of 79,300.
[0147] <Synthesis example 3>
[0148] After adding NMP to the polyamic acid solution (2) (20.0 g) obtained in Synthesis Example 2 to dilute it to 6 mass%, anhydrous acetic acid (2.40 g) and pyridine (1.85 g) as imidization catalysts were added, and the mixture was reacted at 60° C. for 4 hours. The reaction solution was put into methanol (500 ml), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (3). The imidization rate of the polyimide was 58%, Mn was 24100, and Mw was 62100.
[0149] <Synthesis example 4>
[0150] D2 (0.30 g, 1.20 mmol), B2 (0.43 g, 1.21 mmol), C1 (0.53 g, 4.90 mmol) and C2 (1.75 g, 6.11 mmol) were mixed in NMP (10.2 g), reacted at 60° C. for 4 hours, then D1 (2.10 g, 10.7 mmol) and NMP (5.12 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (4) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 23,200 and an Mw of 73,700.
[0151] <Synthesis example 5>
[0152] D2 (1.96 g, 7.83 mmol), B1 (1.60 g, 6.05 mmol), C1 (0.44 g, 4.07 mmol) and C3 (3.83 g, 10.1 mmol) were mixed in NMP (20.2 g), reacted at 80° C. for 4 hours, then D1 (2.30 g, 11.7 mmol) and NMP (10.1 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (5) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 21,800 and an Mw of 66,400.
[0153] <Synthesis example 6>
[0154] NMP was added to the polyamic acid solution (5) (20.0 g) obtained in Synthesis Example 5 to dilute it to 6% by mass, and then anhydrous acetic acid (2.50 g) and pyridine (1.90 g) were added as imidization catalysts, and the mixture was reacted at 80° C. for 4 hours. The reaction solution was put into methanol (500 ml), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (6). The imidization rate of the polyimide was 55%, Mn was 19100, and Mw was 46300.
[0155] <Synthesis Example 7>
[0156] D2 (1.11 g, 4.44 mmol), B2 (1.61 g, 4.54 mmol), C1 (0.62 g, 5.73 mmol) and C4 (0.56 g, 1.14 mmol) were mixed in NMP (10.4 g), reacted at 80° C. for 6 hours, then D1 (1.30 g, 6.63 mmol) and NMP (5.20 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (7) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 20,900 and an Mw of 64,800.
[0157] <Synthesis example 8>
[0158] D3 (2.10 g, 9.37 mmol), B1 (0.77 g, 2.91 mmol), B2 (0.34 g, 0.96 mmol), C1 (0.10 g, 0.92 mmol) and C3 (1.84 g, 4.83 mmol) were mixed in NMP (15.4 g) and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (8) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 19100 and an Mw of 61900.
[0159] <Synthesis Example 9>
[0160] D3 (2.50 g, 11.2 mmol), B1 (0.91 g, 3.44 mmol), C1 (0.62 g, 5.73 mmol) and C4 (1.13 g, 2.29 mmol) were mixed in NMP (15.5 g) and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (9) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 19,800 and an Mw of 63,900.
[0161] <Synthesis Example 10>
[0162] Under a nitrogen atmosphere, B1 (0.51 g, 1.93 mmol), C1 (0.31 g, 2.87 mmol), C2 (1.39 g, 4.85 mmol), pyridine (1.88 g) and NMP (15.1 g) were added, stirred and dissolved, and D4 (2.80 g, 9.43 mmol) was added, and the reaction was carried out at 15 ° C for 15 hours. Then, acryloyl chloride (0.04 g) was added, and the reaction was carried out at 15 ° C for 4 hours. The reaction solution was put into water (500 g), and the obtained precipitate was filtered out. The precipitate was washed with isopropanol and dried under reduced pressure at 100 ° C to obtain a polyamic acid alkyl ester powder (10). The Mn of the polyamic acid alkyl ester is 18500 and the Mw is 40100.
[0163] <Synthesis Example 11>
[0164] D1 (2.40 g, 12.2 mmol), C1 (0.55 g, 5.09 mmol) and C2 (2.17 g, 7.58 mmol) were mixed in NMP (15.3 g) and reacted at 25° C. for 8 hours to obtain a polyamic acid solution (11) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 28,200 and an Mw of 84,200.
[0165] <Synthesis Example 12>
[0166] D2 (2.13 g, 8.51 mmol), C1 (1.18 g, 10.9 mmol) and C3 (4.16 g, 10.9 mmol) were mixed in NMP (20.0 g), reacted at 80° C. for 4 hours, then D1 (2.50 g, 12.7 mmol) and NMP (9.97 g) were added, and reacted at 40° C. for 6 hours to obtain a polyamic acid solution (12) having a resin solid content concentration of 25% by mass. The polyamic acid had an Mn of 23100 and an Mw of 70100.
[0167] Table 4 shows the polyimide polymers obtained in Synthesis Examples 1 to 11.
[0168] [Table 4]
[0169]
[0170] *1: Polyamic acid. *2: Polyamic acid alkyl ester.
[0171] "Manufacturing of liquid crystal alignment agent"
[0172] Production examples of the liquid-crystal aligning agent are described in Examples 1 to 14 and Comparative Examples 1 to 8 described below. In addition, this liquid-crystal aligning agent was also used for evaluation.
[0173] Tables 5 to 7 show the obtained liquid-crystal aligning agents.
[0174] "Storage stability test of liquid crystal alignment agent"
[0175] The storage stability test was performed using the liquid crystal aligning agent obtained in the examples and comparative examples. Specifically, the liquid crystal aligning agent was filtered under pressure using a membrane filter with a pore size of 1 μm and stored at -15°C for 72 hours. Then, the turbidity and precipitate in the liquid crystal aligning agent were confirmed by visual observation. As a result, no turbidity or precipitate was observed in all the liquid crystal aligning agents of the examples and comparative examples, and they were uniform solutions.
[0176] "Evaluation of fit"
[0177] The liquid crystal alignment agent obtained in the embodiment and the comparative example was applied to the ITO surface of a 100 mm × 100 mm PET substrate with an ITO electrode (length: 100 mm, width: 100 mm, thickness: 0.1 mm) washed with pure water by spin coating, and heated on a hot plate at 120° C. for 2 minutes to obtain an ITO substrate with a liquid crystal alignment film having a film thickness of 100 nm. Two pieces of the ITO substrate with a liquid crystal alignment film were prepared and cut into a size of 100 × 20 mm (length × width).
[0178] Next, a 6 μm spacer was applied to the liquid crystal alignment film surface of one substrate, and a sealant (723K1) (manufactured by Kyoritsu Chemical Industry Co., Ltd.) was applied to the liquid crystal alignment film surface of the other substrate, and the two substrates were bonded together in such a way that the liquid crystal alignment film surfaces of the two substrates faced each other. At this time, the amount of sealant applied was adjusted so that the area of the sealant after bonding became 5×50 mm (length×width). Then, an illumination of 20 mW / cm 2 The metal halide lamp irradiates the bonded substrates with a wavelength of 365nm, which is 3J / cm 2 The film was irradiated with ultraviolet rays, and then heat-treated at 120° C. for 60 minutes in a heat circulation type clean oven to produce a cell for adhesion evaluation.
[0179] The evaluation of the adhesion was performed using a desktop precision universal testing machine (AGS-X 500N) (manufactured by Shimadzu Corporation). Specifically, after the upper and lower ends of the obtained unit were fixed, the breaking strength (N) when stretched in the vertical direction was measured. In terms of evaluation, the larger the value of the breaking strength, the better the adhesion, that is, it was set as excellent in this evaluation.
[0180] The results are shown in Tables 8 to 10.
[0181] "Production of liquid crystal display elements and evaluation of their resistance to constant temperature and humidity"
[0182] The liquid crystal alignment agent obtained in the embodiment and the comparative example was filtered under pressure using a membrane filter with a pore size of 1 μm, and then spin-coated on the ITO surface of a substrate (length 40 mm × width 30 mm, thickness 0.7 mm) with an ITO electrode washed with pure water and IPA, and heated on a hot plate at 120°C for 2 minutes, and heated in a thermal cycle clean oven at 230°C for 30 minutes to obtain an ITO substrate with a liquid crystal alignment film having a film thickness of 100 nm. Next, the liquid crystal alignment film surface of the substrate was brushed using a brushing device with a roller diameter of 120 mm, using a rayon cloth, at a roller speed of 500 rpm, a roller travel speed of 30 mm / sec, and a press amount of 0.3 mm.
[0183] Then, prepare two brushed substrates, apply a 4μm spacer to the liquid crystal orientation film surface of one substrate, apply a sealant (XN-1500T) (manufactured by Kyoritsu Chemical Industry Co., Ltd.) to the liquid crystal orientation film surface of the four sides of the other substrate, and bond the two substrates in a manner that the liquid crystal orientation film surfaces face each other. At this time, bond the substrates in such a manner that the brushing directions of each substrate are in opposite directions. Next, heat treatment is performed at 120°C for 90 minutes in a thermal cycle clean oven to produce an empty unit. Liquid crystal is injected into the empty unit by a reduced pressure injection method, and the injection port is sealed to obtain a liquid crystal unit. It should be noted that in Examples 1 to 5, 13, 14, Comparative Examples 1, 3, 5, and 7, positive liquid crystal (MLC-2003) (manufactured by MERCK) is used for the liquid crystal, and in Examples 6 to 12, Comparative Examples 2, 4, 6, and 8, negative liquid crystal (MLC-6608) (manufactured by MERCK) is used for the liquid crystal.
[0184] By observation using a polarizing microscope (ECLIPSE E600WPOL) (manufactured by Nikon Corporation), it was confirmed that all the liquid crystal cells obtained in Examples and Comparative Examples showed uniform liquid-crystal orientation.
[0185] Then, the liquid crystal cell was kept in a constant temperature and humidity chamber at a temperature of 80 ° C and a humidity of 90% RH for 48 hours, and the peeling of the liquid crystal cell and the presence or absence of bubbles were confirmed. Specifically, the liquid crystal cell that did not produce peeling (the state of peeling between the liquid crystal alignment film and the sealant and between the liquid crystal alignment film and the ITO electrode) and the liquid crystal cell that did not produce bubbles in the liquid crystal cell were set as excellent in this evaluation (good display in the table). At this time, in Examples 2, 3, 7, 8, 11, and 12, in addition to the standard test described, as an emphasis test, it was also kept in a constant temperature and humidity chamber at a temperature of 80 ° C and a humidity of 90% RH for 144 hours and confirmed. It should be noted that the evaluation method is the same as above.
[0186] The results are shown in Tables 8 to 10.
[0187] <Example 1>
[0188] A1 (0.20 g), NMP (23.8 g), and BCS (7.83 g) were added to the polyamic acid solution (1) (10.0 g) obtained in Synthesis Example 1, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (1).
[0189] <Example 2>
[0190] A1 (0.30 g), NMP (23.8 g), and BCS (7.83 g) were added to the polyamic acid solution (2) (10.0 g) obtained in Synthesis Example 2, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (2).
[0191] <Example 3>
[0192] A1 (0.30 g), K1 (0.18 g), NMP (23.8 g), and BCS (7.83 g) were added to the polyamic acid solution (2) (10.0 g) obtained in Synthesis Example 2, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (3).
[0193] <Example 4>
[0194] NEP (31.3 g) was added to the polyimide powder (3) (2.50 g) obtained in Synthesis Example 3, and dissolved by stirring at 60° C. for 24 hours. A2 (0.15 g) and BCS (7.83 g) were added to the solution, and stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (4).
[0195] <Example 5>
[0196] A1 (0.13 g), A2 (0.075 g), NMP (19.9 g), BCS (7.83 g) and PB (3.92 g) were added to the polyamic acid solution (4) (10.0 g) obtained in Synthesis Example 4, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (5).
[0197] <Example 6>
[0198] A1 (0.15 g), NMP (16.0 g), and BCS (15.7 g) were added to the polyamic acid solution (5) (10.0 g) obtained in Synthesis Example 5, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (6).
[0199] <Example 7>
[0200] NEP (23.5 g) was added to the polyimide powder (6) (2.50 g) obtained in Synthesis Example 6, and the mixture was stirred at 60° C. for 24 hours to dissolve. A2 (0.20 g) and PB (15.7 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (7).
[0201] <Example 8>
[0202] NEP (23.5 g) was added to the polyimide powder (6) (2.50 g) obtained in Synthesis Example 6, and the mixture was stirred at 60° C. for 24 hours to dissolve the mixture. A2 (0.20 g), K1 (0.18 g) and PB (15.7 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (8).
[0203] <Example 9>
[0204] A1 (0.10 g), K2 (0.08 g), NMP (19.9 g), BCS (7.83 g) and PB (3.92 g) were added to the polyamic acid solution (7) (10.0 g) obtained in Synthesis Example 7, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (9).
[0205] <Example 10>
[0206] A2 (0.15 g), K2 (0.18 g), NMP (19.9 g) and BCS (11.8 g) were added to the polyamic acid solution (8) (10.0 g) obtained in Synthesis Example 8, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (10).
[0207] <Example 11>
[0208] A1 (0.23 g), NMP (19.9 g) and BCS (11.8 g) were added to the polyamic acid solution (9) (10.0 g) obtained in Synthesis Example 9, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (11).
[0209] <Example 12>
[0210] A1 (0.23 g), K1 (0.13 g), NMP (19.9 g) and BCS (11.8 g) were added to the polyamic acid solution (9) (10.0 g) obtained in Synthesis Example 9, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (12).
[0211] <Example 13>
[0212] NMP (31.3 g) was added to the polyamic acid alkyl ester powder (10) (2.50 g) obtained in Synthesis Example 10, and the mixture was dissolved by stirring at 40° C. for 24 hours. A1 (0.30 g) and BCS (7.83 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (13).
[0213] <Example 14>
[0214] NEP (31.3 g) was added to the polyamic acid alkyl ester powder (10) (2.50 g) obtained in Synthesis Example 10, and the mixture was stirred at 40° C. for 24 hours to dissolve the mixture. A2 (0.20 g), K2 (0.13 g) and BCS (7.83 g) were added to the solution, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid crystal aligning agent (14).
[0215] <Comparative Example 1>
[0216] NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (11) (10.0 g) obtained in Synthesis Example 11, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (15).
[0217] <Comparative Example 2>
[0218] NMP (16.0 g) and BCS (15.7 g) were added to the polyamic acid solution (12) (10.0 g) obtained in Synthesis Example 12, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (16).
[0219] <Comparative Example 3>
[0220] A1 (0.20 g), NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (11) (10.0 g) obtained in Synthesis Example 11, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (17).
[0221] <Comparative Example 4>
[0222] A1 (0.15 g), NMP (16.0 g) and BCS (15.7 g) were added to the polyamic acid solution (12) (10.0 g) obtained in Synthesis Example 12, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (18).
[0223] <Comparative Example 5>
[0224] NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (1) (10.0 g) obtained in Synthesis Example 1, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (19).
[0225] <Comparative Example 6>
[0226] NMP (16.0 g) and BCS (15.7 g) were added to the polyamic acid solution (5) (10.0 g) obtained in Synthesis Example 5, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (20).
[0227] <Comparative Example 7>
[0228] a1 (0.20 g), NMP (23.8 g) and BCS (7.83 g) were added to the polyamic acid solution (1) (10.0 g) obtained in Synthesis Example 1, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (21).
[0229] <Comparative Example 8>
[0230] a1 (0.15 g), NMP (16.0 g) and BCS (15.7 g) were added to the polyamic acid solution (5) (10.0 g) obtained in Synthesis Example 5, and the mixture was stirred at 25° C. for 15 hours to obtain a liquid-crystal aligning agent (22).
[0231] <Examples 1 to 14 and Comparative Examples 1 to 8>
[0232] Using the liquid-crystal aligning agents (1) to (22) obtained above, “evaluation of adhesion” and “production of liquid crystal display element and evaluation of constant temperature and humidity resistance” were performed under the above-mentioned conditions.
[0233] In addition, in these liquid-crystal aligning agents (1)-(22), abnormality, such as turbidity and precipitation, was not observed, and it was confirmed that it was a uniform solution.
[0234] [Table 5]
[0235] Liquid crystal alignment agent Polyimide polymers Specific compound*3 Specific compounds*4 Example 1 Liquid crystal alignment agent (1) Polyamic acid solution (1) A1(8) - Example 2 Liquid crystal alignment agent (2) Polyamic acid solution (2) A1(12) - Example 3 Liquid crystal alignment agent (3) Polyamic acid solution (2) A1(12) K1(7) Example 4 Liquid crystal alignment agent (4) Polyimide powder(3) A2(6) - Example 5 Liquid crystal alignment agent (5) Polyamic acid solution (4) A1(5), A2(3) - Example 6 Liquid crystal alignment agent (6) Polyamic acid solution (5) A1(6) - Example 7 Liquid crystal alignment agent (7) Polyimide powder(6) A2(8) - Example 8 Liquid crystal alignment agent (8) Polyimide powder(6) A2(8) K1(7) Example 9 Liquid crystal alignment agent (9) Polyamic acid solution (7) A1(4) K2(3) Example 10 Liquid crystal alignment agent (10) Polyamic acid solution (8) A2(6) K2(7)
[0236] [Table 6]
[0237]
[0238] [Table 7]
[0239]
[0240] *3: It shows the content (parts by mass) of a specific compound based on 100 parts by mass of a polymer.
[0241] *4: It shows the content (parts by mass) of the crosslinking compound based on 100 parts by mass of the polymer.
[0242] [Table 8]
[0243]
[0244] [Table 9]
[0245]
[0246] [Table 10]
[0247]
[0248] *5: Very small amount of bubbles were observed inside the element.
[0249] *6: A small amount of bubbles (more than *5) were observed inside the element.
[0250] *7: Bubbles were observed inside the element (more than *6).
[0251] *8: A large number of bubbles were observed inside the element (more than *7).
[0252] According to the above results, compared with the comparative examples of the liquid crystal aligning agent not containing the specific compound and the specific polymer, or containing only one of the specific compound and the specific polymer, the embodiment using the liquid crystal aligning agent containing the specific compound and the specific polymer has excellent adhesion, and even if the liquid crystal cell is stored for a long time under high temperature and high humidity, the liquid crystal cell does not peel off. Specifically, the comparison under the same conditions is the comparison between Example 1 and Comparative Example 1, Comparative Example 3 and Comparative Example 5, and the comparison between Example 6 and Comparative Example 2, Comparative Example 4 and Comparative Example 6.
[0253] In addition, compared with the comparative example of the liquid crystal aligning agent containing a compound having two thiol groups, the above-mentioned characteristics of the embodiment using the liquid crystal aligning agent containing a specific compound having three or more thiol groups in the molecule are excellent. Specifically, the comparison under the same conditions is the comparison between Example 1 and Comparative Example 7, and the comparison between Example 6 and Comparative Example 8.
[0254] In addition, when a crosslinking compound was introduced into the liquid crystal aligning agent, no bubbles were generated in the liquid crystal cell in the stress test. Specifically, the comparison under the same conditions was a comparison between Example 2 and Example 3, a comparison between Example 7 and Example 8, and a comparison between Example 11 and Example 12.
[0255] Industrial Applicability
[0256] As for the liquid crystal aligning agent of the present invention, by using the liquid crystal aligning film obtained therefrom, it is possible to obtain a liquid crystal display element having high adhesion between substrates, and even if it is exposed to a harsh environment of high temperature and high humidity for a long time, it is possible to suppress the generation of bubbles in the liquid crystal display element and the peeling of the element. Therefore, it can be preferably used for liquid crystal display elements of smart phones, mobile phones, etc.
[0257] It should be noted that all the contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2018-246262 filed on December 27, 2018 are cited herein and introduced as a disclosure of the specification of the present invention.
Claims
1. A liquid crystal alignment agent, wherein Contains the following components A and B, Component A: a compound having three or more thiol groups in its molecule, Component B: at least one polymer selected from the group consisting of a polyimide precursor obtained by reacting a diamine component containing a diamine having a structure represented by the following formula [1] with a tetracarboxylic acid component, and a polyimide obtained by imidating the polyimide precursor, -X1——X2——X3——X4[1] In the formula, X 1 , X 3 Each independently represents at least one selected from the group consisting of a single bond, -O-, -NH-, -N(CH3)-, -CH2O-, -CONH-, -NHCO-, -CON(CH3)-, -N(CH3)CO-, -COO-, and -OCO-, and X 2 represents an alkylene group having 1 to 18 carbon atoms, or an organic group having 6 to 24 carbon atoms having at least one cyclic group selected from a benzene ring, a cyclohexane ring and a heterocyclic ring, wherein any hydrogen atom on the cyclic group is optionally substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorinated alkyl group having 1 to 3 carbon atoms, a fluorinated alkoxy group having 1 to 3 carbon atoms, or a fluorine atom, and X 4 represents at least one selected from the group consisting of the following formulas [1-a] to [1-g], In the formula, Xa represents a hydrogen atom or a benzene ring, b represents at least one selected from the group consisting of a single bond, a benzene ring, a cyclohexane ring and a heterocyclic ring, and X c It represents an alkyl group having 1 to 18 carbon atoms, a fluorinated alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, or a fluorinated alkoxy group having 1 to 18 carbon atoms.
2. The liquid crystal alignment agent according to claim 1, wherein The component A is selected from 1,2,3-propanetrithiol, 1,2,4-butanetrithiol, pentaerythritol tris(3-mercaptopropionate), 1,3,5-benzenetrithiol, 2,4,6-mesitylenetrithiol, neopentanetetrathiol, 2,4,6-toluenetrithiol, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, dipentaerythritol hexa(3-mercaptopropionate), trimethylolpropane At least one of the group consisting of tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6-(1H.3H.5H)-trione, 2,2'-bis(mercaptomethyl)-1,3-propanedithiol, pentaerythritol tetrakis(3-mercaptopropionate) or dipentaerythritol hexa(3-mercaptopropionate).
3. The liquid crystal alignment agent according to claim 1, wherein The component A is trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, dipentaerythritol hexa(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetra(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6-(1H.3H.5H)-trione or neopentanetetrathiol, pentaerythritol tetra(3-mercaptopropionate), or dipentaerythritol hexa(3-mercaptopropionate).
4. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein The component A is contained in an amount of 0.1 to 30 parts by mass based on 100 parts by mass of the polymer.
5. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein The diamine having a structure represented by the above formula [1] is a diamine represented by the following formula [1a]: In the formula, X represents the structure represented by the formula [1], and n represents an integer of 1 to 4.
6. The liquid crystal alignment agent according to claim 5, wherein The diamine represented by the formula [1a] is a diamine of any one of the following formulas [1a-1] to [1a-9], n represents an integer from 2 to 12.
7. The liquid crystal alignment agent according to claim 5, wherein The diamine represented by the formula [1a] is a diamine of the following formula B1 or B2, 8. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein The diamine having the structure represented by the formula [1] is contained in an amount of 1 to 50 mol% based on the total amount of the diamine component.
9. The liquid crystal aligning agent according to any one of claims 1 to 3, wherein The invention comprises at least one crosslinking compound selected from the following: a crosslinking compound having a group selected from an epoxy group, an isocyanate group, an oxetane group and a cyclocarbonate group; a crosslinking compound having a group selected from a hydroxyl group, a hydroxyalkyl group and an alkoxyalkyl group having 1 to 3 carbon atoms; or a crosslinking compound having a polymerizable unsaturated bond group.
10. The liquid crystal alignment agent according to claim 9, wherein The cross-linking compound is a compound represented by the following formula K1 or K2, 11. The liquid crystal alignment agent according to claim 9, wherein The crosslinking compound is contained in an amount of 0.1 to 100 parts by mass based on 100 parts by mass of the polymer. 12 . A liquid crystal aligning film obtained from the treating agent for liquid crystal aligning according to claim 1 . 13 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 12 .
14. The liquid crystal display element according to claim 13, wherein The liquid crystal display element is a mobile device.
Citation Information
Patent Citations
Soluble polyimide resin composition
JP1986171762A
Liquid crystal orientation agent
JP1999119226A
Liquid-crystal alignment agent, liquid-crystal alignment film, and liquid-crystal display element
WO2011132751A1
Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element
WO2012014898A1
Liquid crystal display element, liquid crystal alignment film and liquid crystal aligning agent
WO2014171493A1